(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Massiseng ANA, Tuwo A, Fachry ME, Bahar A. 2022. Characteristics of plastic waste and perceptions of coastal communities in the MLC Baluno mangrove ecotourism area, West Sulawesi, Indonesia. Biodiversitas 23: 6262-6274. Plastic pollution is a global problem that threatens coastal and marine ecosystems and human livelihoods and requires effective solutions that can be adapted to local conditions. Management of coastal areas is one sector focusing on world development in general and Indonesia in particular. This research was conducted from July to October 2021 in the mangrove ecotourism area of ??MLC Baluno, Sendana Sub-district, Majene District, West Sulawesi Province, Indonesia. The type of data used is the primary data from measurements and observations at ecotourism sites. The purpose of this study was to identify the characteristics of plastic waste and analyze its impact on the socio-economic community in the MLC Baluno mangrove ecotourism area. The results showed (1) The percentage of plastic waste types from all observation stations in the MLC Baluno mangrove ecotourism area consisted of 22% HDPE, 20% LDPE, 17% PVC, 9% PETE, 12% PE, 10% PP, 6 % PE, and 4% PU, (2) The volume percentage of plastic waste from observation stations in the mangrove ecotourism area of ??MLC Baluno by type consists of 32% PVC plastic volume, 17% HDPE, 14% PE, 10% LDPE, 10% PETE, PP 11%, 4% PS and 2% PU, (3) The influence of plastic waste factors (types and volume) has a positive effect on the socio-economic community (livelihood and income). The variable factors of plastic waste influencing socio-economic based on the perceptions of coastal communities in the MLC Baluno mangrove ecotourism area are TW2, VW3, VW4, LV1, LV2, IC1, IC3, and IC5.